Step-by-step explanation:
let necklace : x
let earrings : y
x+y=144 -1st eqn
6x+5y=825 -2nd eqn
y=144-X -3rd eqn
substitute eqn into 2nd eqn
6x+5(144-x)= 825
6x +720-5X =825 (expanded)
X = 825-720
X =105
substitute "X=105" into 1st eqn
(105)+y=144
y= 144-105
y=39
1 necklace = 105$
1 pair of earrings = 39$
(to check back: substitute the value into the original eqn)
The line plot shows it increases
Answer:
1r
Step-by-step explanation:
(5r-4)(2r-6r+4)
1(5r-4)+1(2r-6r+4)
5r-4+2r-6r+4
5r+2r-6=1r
1r-4+4
-4+4=0
1r
Answer:
j = -8
Step-by-step explanation:
-13j - 20 = -8j + 20
Add 13 j to each side
-13j+13j - 20 = -8j+13j + 20
-20 = 5j+20
subtract 20 from each side
-20-20 = 5j +20-20
-40 = 5j
Divide by 5
-40/5 = =5j/5
-8 =j